Hedgehog-regulated atypical PKC promotes phosphorylation and activation of Smoothened and Cubitus interruptus in Drosophila. - Jiang, K.; Liu, Y.; Fan, J.; Epperly, G.; Gao, T.; Jiang, J.; Jia, J. (Proceedings of the National Academy of Sciences of the United States of America, 2014)
Smoothened (Smo) is essential for transduction of the Hedgehog (Hh) signal in both insects and vertebrates. Cell surface/cilium accumulation of Smo is thought to play an important role in Hh signaling, but how the localization of Smo is controlled remains poorly understood. In this study, we demonstrate that atypical PKC (aPKC) regulates Smo phosphorylation and basolateral accumulation in Drosophila wings. Inactivation of aPKC by either RNAi or a mutation inhibits Smo basolateral accumulation and attenuates Hh target gene expression. In contrast, expression of constitutively active aPKC elevates basolateral accumulation of Smo and promotes Hh signaling. The aPKC-mediated phosphorylation of Smo at Ser680 promotes Ser683 phosphorylation by casein kinase 1 (CK1), and these phosphorylation events elevate Smo activity in vivo. Moreover, aPKC has an additional positive role in Hh signaling by regulating the activity of Cubitus interruptus (Ci) through phosphorylation of the Zn finger DNA-binding domain. Finally, the expression of aPKC is up-regulated by Hh signaling in a Ci-dependent manner. Our findings indicate a direct involvement of aPKC in Hh signaling beyond its role in cell polarity.